Eye on Denver: Peak performances at the American Academy of Optometry in Denver, CO - Dalton, Kristine; Bitton, Etty (Canadian Journal of Optometry, 2015)
The annual American Academy of Optometry (AAO) meeting had another record-breaking year in Denver this past november. A total of 6,323 attendees made this meeting the largest on record, despite the sub-zero temperatures and biting winds. Among the attendees were 218 Canadian optometrists and 71 students, residents, and librarians from both Canadian schools. Overall student attendance hit a record high this year, with 995 optometry students attending in total. the faculty and students from the two Canadian schools were once again very involved in the meeting, presenting posters, research talks, and Ce lectures and being honoured with awards.